SUNDANESE LANGUAGE ACQUISITION IN CHILDREN WITH INDONESIAN MOTHER LANGUAGE - Triyanto Triyanto (STKIP Siliwangi, 2021)
Since childhood, humans acquire language acquisition. Language acquisition by a child is obtained from the immediate environment, namely the family environment and social environment. The language that a child acquires through acquisition is called the mother tongue. However, the mother tongue that a child gets is sometimes not in a single way, but it goes along with other languages because of differences in language in the family environment and language in the social environment, making a child a bilingual speaker. Based on this description, this study aims to examine the acquisition of Sundanese (L2) in a child who speaks an Indonesian mother tongue (L1). The method used is qualitative. Data collection was carried out by listening to the conversation between the MKI (research object) with the family and with other parties in their social environment. Other data collection conducted by interviewing the MKI. The collected data were analyzed using psycholinguistic, syntactic, and phonological theories and then described using a descriptive approach. The results showed that MKI has a performance in Sundanese both receptive performance and productive performance. Productive performance in the form of lexicon, phoneme pronunciation, and sentences. Keywords: language acquisition, bilingual, receptive performance, productive performance